Transparent Schottky Photodiodes: Transparent Schottky Photodiode Based on AgNi NWs/SrTiO3 Contact with an Ultrafast Photoresponse to Short‐Wavelength Blue Light and UV‐Shielding Effect (Adv. Funct. Mater. 46/2019). (12th November 2019) - Yang, Wei; Zhang, Yong; Zhang, Yujia; Deng, Wanjun; Fang, Xiaosheng
Abstract : In article number 1905923, Xiaosheng Fang and co‐workers fabricate nickel‐coated silver nanowires to form a transparent electrode with an enhanced work function value, which supports a transparent Schottky photodiode combining UV filtering and bias‐free photodetection to short‐wavelength blue light. This work proposes a method to modulate the work function of transparent silver nanowire electrodes by surface coating.